FAKTOR-FAKTOR YANG MEMPENGARUHI FUNGSI MENTORING PADA KANTOR AKUNTAN PUBLIK DIKOTA MALANG - Karlina Dwika Nurcahyani; Nur Diana (Universitas Islam Malang, 2018)
ABSTRACTThis study aims to determine the influence and relationship of mentoring function(social suport, career delvelopment, and role modeling) Public Accounting Firm in Malang.The population in this study is all Public Accounting Firm in Malang. While the sample inthis study is the Public Accounting Firm registered in the Indonesian Institute of CertifiedAccountants. The sampling technique is done by Pusposive Sampling method. The samplewas 115 questionnaires. This data is obtained from partners, managers, senior auditors, juniorauditors, staff, and firm partners. Data analysis is done by using multiple linear regressionmethod. The results of this study indicate that (1) The structure of the Public AccountingFirm influences the function mentoring of social support, career development, and rolemodeling (2) Protégés gender does not affect the function mentoring of social support , careerdevelopment, and role modeling (3) Mentoring functions does not effect the functionmentoring of social support, career development, and role modeling.Keywords: Public Accountant Firm Structure, Protégés Gender, Position Mentoring, andMentoring Function.